THE EFFECT OF USING BLOOM’S TAXONOMY-BASED LESSON PLANNING ON DEVELOPING SPEAKING SKILLS IN EFL CLASSROOMS - Risqulova Shohsanam Avazbek kizi (International Journal of Literature and Language Studies, 2026)
This study investigates the effect of using Bloom’s Taxonomy-based lesson planning on the development of speaking skills among English as a Foreign Language (EFL) learners. A quasi-experimental design was employed with 40 intermediate-level students divided into an experimental group and a control group. The experimental group received instruction through lessons structured according to Bloom’s Taxonomy, while the control group was taught using traditional methods. Data were collected through pre- and post-speaking tests and classroom observations. The results indicate that students in the experimental group demonstrated greater improvement in speaking fluency, coherence, and confidence. The findings suggest that structured lesson planning based on cognitive levels enhances learners’ ability to produce meaningful spoken language. The study highlights the importance of integrating higher-order thinking skills into EFL lesson design.